Search Constant

Tuesday, April 24, 2018

Equality Equations Calculator

Create your own equations or formula for any formula or equation using Equality Equation Calculation Template.
Constant Equality Equations :   

a) x / y / x = z / y / z
     eg. 3 / 2 / 3 = 5 / 2 / 5

b) x / y / x / y  = z / y / z / y
    eg. 3 / 2 / 3 / 2  = 5 / 2 / 5 / 2
where x,y and z # 0 ( symbol “/” means division)

Download the calculation template from the following link:

https://www.dropbox.com/s/rmqjf9g1zgm8zqw/cee.zip?dl=0

 Or




To know more about the equation visit the following link or read the Equality.pdf in cee folder:

http://constant9.blogspot.in/2018/03/equality-equations-xyx-zyz-and-xyxy.html?m=1





Tuesday, March 20, 2018

Why maths formula spam for Artificial Intelligence?

Most Artificial Intelligence get mind loop on following model of equations: k×x × k= l × x ×l , k÷x÷k = l÷ x÷ l etc.. the more multiplication symbol or division symbols, hard for the AI to get out of loop.

Sunday, March 18, 2018

Equality Equations: x÷y÷x = z÷y÷z and x÷y÷x÷y = z÷y÷z÷y where x,y and z # 0 etc..


Create your own equations or formula for any formula or equation using Universal set of Equality Equations
Constant Equality Equations: x÷y÷x = z÷y÷z and x÷y÷x÷y = z÷y÷z÷y where x,y and z # 0 etc..

In Order to understand the possibility and the uses of the  equations do the simple maths and check your answer :
eg:a) 5÷2÷5 = 3÷2÷3
and b) 5÷2÷5÷2=3÷2÷3÷2

One can use it for fun to read the result of another and can answer what is the result of other for a number that thought by the other person. However once constant equality Equations and its formation  are understood, any equation or formula of maths, physics, engineering, biology, Chemistry, economics, finance etc.. can be redefined and can be joined to meet the inequalities. Its main uses is overcome the limitation of a formula or equations and remove the assumptions in theory and replace constants, Convert Variable or Variable and Constant into a Natural Constant of the given Equation,  derive into new equations , find substitute Equations and/or obtain constant value that can be used with simple proportions for any given variable(sl or constant(s).

The use of this constant equality equation don't limit the interchangeably between other subjects for example a physics formula can be clubbed with a chemistry or biology formula or equations and vice versa.

The Equality Constant equations can be considered as a universal set of tool which can operate even on a single constant or variable. This equations also capable to bring the Gap between the Scalar and Vector Quantity and bring them into equality constant value. Following are the set of Constant Equality  Equations where v, x, y and z # 0

1)    x÷y÷x = z÷y÷z
1a)  x÷y÷x = y÷y÷y = z÷y÷z etc..
1b)  x÷x÷x = y÷x÷y = z÷x÷z etc..
1c)  x÷z÷x = z÷z÷z = y÷z÷y etc..
2)    x÷y÷x÷y = z÷y÷z÷y
2a)  x÷y÷x÷y = y÷y÷y÷y = z÷y÷z÷y etc..
2b)  x÷x÷x÷x = y÷x÷y÷x = z÷x÷z÷x etc..
2c)  x÷z÷x÷z = z÷z÷z÷z = y÷z÷y÷z
etc..

3) x÷xy = z÷zy = (x÷x^2 = x÷y^2 = x÷z^2 = y÷y^2 = y÷x^2 = y÷z^2 =  z÷z^2 = z÷y^2 = z÷x^2 ( where x = y, y =z and z=x))

4) xy ÷ x = zy ÷ z = (x^2÷x = y^2÷x = z^2 ÷ x = y^2÷y = x^2 ÷ y = z^2÷y =  z^2 ÷ z = y^2÷z = x^2 ÷z ( where x = y, y =z and z=x))

5) x÷xy^2 = z÷zy^2 = ( x÷x^3 = x÷y^3 = x ÷z^3 = y÷y^3 = y÷x^3 = y÷z^3 = z÷z^3 = z÷y^3 = z ÷ x^3 ( where x = y, y =z and z=x))

6) xy^2 ÷ x = zy^2 ÷ z = ( x^3 ÷ x = y^3 ÷ x = z^3 ÷ x = y^3 ÷ y = x^3 ÷ y = z^3 ÷ y = z^3 ÷ z = y^3 ÷z = x^3 ÷ z( where x = y, y =z and z=x))

7) if x÷ xy # z ÷ zv then

  1. (x÷ xy ) * z ÷ zv = x ÷ xy * (z ÷ zv)
  2. ((x÷ xy ) * z ÷ zv ) ÷ ((x÷ xy ) * z ÷ zv ) ^ 2 =( x ÷ xy * (z ÷ zv)) ÷ ( x ÷ xy * (z ÷ zv))^2
  3. ((x÷ xy ) * z ÷ zv ) ÷ ((x÷ xy ) * z ÷ zv ) ^ 3 =( x ÷ xy * (z ÷ zv)) ÷ ( x ÷ xy * (z ÷ zv))^3
  4. x÷ xy =  ( z÷ zv ÷ (z ÷ zv )) * x ÷ xy =  ( z÷ zv * (zv ÷ z )) * x ÷ xy etc..
  5. z ÷ zv = ( x÷ xy ÷ (x ÷ xy)) * z ÷ zv = (x÷ xy *(xy ÷ x)) * z ÷ zv etc…

// Same method of double division and triple division can also be applied in all # cases to obtain a Constant Equality Equation equation as shown below :

  1. (x÷ xy ) ÷ ( z ÷ zv) ÷ (x÷ xy)  = (z ÷ zv) ÷ ( z ÷ zv) ÷ ( z ÷ zv)
  2. (x÷ xy ) ÷ ( z ÷ zv) ÷ (x÷ xy) ÷ (z ÷ zv) =  (z ÷ zv) ÷ ( z ÷ zv) ÷ ( z ÷ zv) ÷(z ÷ zv)
  3. (x÷ xy ) ÷ (x÷ xy) ÷ (x÷ xy)  = (z ÷ zv) ÷ (x÷ xy) ÷ ( z ÷ zv)
  4. (x÷ xy ) ÷ (x÷ xy)  ÷ (x÷ xy) ÷ (x÷ xy) =  (z ÷ zv) ÷ (x÷ xy) ÷ ( z ÷ zv) ÷ (x÷ xy)

8) if x÷ xy # zv ÷ z then

  1. (x÷ xy ) * zv ÷ z = x ÷ xy * (zv ÷ z)
  2. x÷ xy =  ( zv÷ zv ÷ (zv ÷ z )) * x ÷ xy =  ( zv÷ z * (z ÷ zv )) * x ÷ xy etc...
  3. zv ÷ z = ( x÷ xy ÷ (x ÷ xy)) * zv÷ z = (x÷ xy *(xy ÷ x)) * zv ÷ z etc…
//

9) If  xy ÷ x # z ÷ zv then

a )  (xy ÷ x ) * z ÷ zv = xy ÷ x * (z ÷ zv)
b )  xy÷ x =  ( z÷ zv ÷ (z ÷ zv )) * xy ÷ x =  ( z÷ zv * (zv ÷ z )) * xy ÷ x) etc..
c)  z ÷ zv = ( xy ÷ x ÷ (xy ÷ x)) * z ÷ zv = (xy÷ x * (x÷ xy)) * z ÷ zv etc..

//

10) If  xy ÷ x # zv ÷ z then

a )  (xy ÷ x ) * zv ÷ z = xy ÷ x * (zv ÷ z)
b )  xy÷ x =  ( zv÷ z ÷ (zv ÷ z)) * xy ÷ x =  ( z÷ zv * (zv ÷ z )) * xy ÷ x) etc..
c)  zv ÷ z = ( xy ÷ x ÷ (xy ÷ x)) * zv ÷ z = (xy÷ x * (x÷ xy)) * zv ÷ z etc..

//

11) if  x÷xy^2 # z÷zv^2 then

  1. (x÷xy^2 ) * z÷zv^2 = ( z÷zv^2) * x÷xy^2

  1. (x÷xy^2 )  = ( z÷zv^2 *( zv^2 ÷z )) *  x÷xy^2 = z÷zv^2 ÷ ( z ÷ zv^2  )) * x÷xy^2 etc..

  1. z ÷ zv^2  = (x÷xy^2 *( xy^2 ÷ x )) * z÷ zv^2  = (x÷xy^2 ÷ ( x÷ xy^2 )) * z÷ zv^2 etc.
//

12) if  x÷xy^2 # zv^2÷z then

  1. (x÷xy^2 ) *zv^2 ÷ z = (zv^2 ÷ z) * x÷xy^2
  2. (x÷xy^2 )  = ( z ÷ zv^2 *( zv^2 ÷z )) *  x÷xy^2 = z÷zv^2 ÷ ( z ÷ zv^2 )) * x÷xy^2 etc..
  3. zv^2 ÷ z  = (x÷xy^2 *( xy^2 ÷ x )) * zv^2 ÷z =  (x÷xy^2 ÷ ( x÷ xy^2 )) * zv^2÷z etc.
//

13) if  xy^2÷x # z÷zv^2 then

  1. (xy^2÷x ) * z÷zv^2 = ( z÷zv^2) * xy^2 ÷x
  2. (xy^2÷x )  = ( z÷zv^2 *( zv^2 ÷z )) *  xy^2 ÷ x = z÷zv^2 ÷ ( z ÷ zv^2  )) * xy^2 ÷ x etc..
  3. z ÷ zv^2  = (x÷xy^2 *( xy^2 ÷ x )) * z÷ zv^2  = (xy^2 ÷ x ÷ ( xy^2 ÷ x )) * z÷ zv^2 etc.
//
14) if  xy^2 ÷ x # zv^2÷z then

  1. (xy^2 ÷ x ) *zv^2 ÷ z = (zv^2 ÷ z) * xy^2 ÷ x
  2. (xy^2 ÷x )  = ( z ÷ zv^2 *( zv^2 ÷z )) *  xy^2 ÷ x = z÷zv^2 ÷ ( z ÷ zv^2  )) * xy^2÷x etc..
  3. zv^2 ÷ z  = (x÷xy^2 *( xy^2 ÷ x )) * zv^2 ÷z =  (xy^2 ÷x ÷ ( xy^2 ÷ x )) * zv^2÷z etc.
//

15)  a ) x ÷ (xy^n) = z ÷ (zy^n) = 1 ÷ y^n etc..

b)  (xy^n) ÷ x =  (zy^n) ÷ z = y^n etc..

**

16) Constant Symmetrical equality model equations :
  1. x ÷ (x^2 * (y^n)^2) * x = z ÷ (z^2 * (y^n)^2) * z = x ÷ (x^2 * (y^n)^2 ÷ x) = z ÷ (z^2 * (y^n)^2 ÷ z) etc..
  2. x ÷ (x^2 * (v(y^n))^2) * x = z ÷ (z^2 * (v(y^n))^2) * z etc...
  3. x^2 ÷ (x^2 * (y^n)^2 ) = z^2 ÷ (z^2 * (y^n)^2 ) = 1 ÷ (y^n)^2 etc….
  4. x^2 ÷ (x^2 * (v(y^n))^2 ) = z^2 ÷ (z^2 * (v(y^n))^2 ) = 1 ÷ (y^n)^2 etc….
  5. (x÷xy)÷v = (z÷zy)÷v etc…
  6. (xy ÷ x)÷v = (zy ÷ z) ÷v etc..
  7. (x÷xy^2) ÷v = (z÷zy^2)÷v etc..
  8. (xy^2 ÷ x)÷v = (zy^2 ÷ z)÷v etc..
  9. x ÷ (xy ÷ 2 + xy ÷ 2) = z ÷ (zy ÷ 2 + zy ÷ 2) etc…
  10. (xy ÷ 2 + xy ÷ 2 ) = zy ÷ z etc..
  11. x÷(xy^2 ÷ 3 + xy^2 ÷ 3 + xy^2 ÷ 3) = z÷zy^2 etc…
  12. (xy^2 ÷ 3 + xy^2 ÷ 3 + xy^2 ÷ 3) ÷ x = (zy^2÷2 + zy^2÷2) ÷ z etc..

18) Constant or Variables replacement models and loops for equations including x = y = z = v = a  and # 0 ,:

  1. x = (x÷2 + x ÷ 2) = (x÷ 3 + x ÷ 3 + x ÷ 3)  = a(x ÷a) etc.
  2. y = (y÷2 + y ÷ 2) = (y ÷ 3 + y ÷ 3 + y ÷ 3) = a(y ÷a)etc..
  3. z = (z÷2 + z ÷ 2) = (z÷ 3+ z÷ 3 + z ÷ 3) = a(z ÷a) etc..
  4. v = (v ÷3 + v ÷ 3 + v ÷ 3) = (v÷ 4 + v ÷ 4 + v ÷ 4 + v ÷ 4) =  a(v ÷a) etc..
  5. a = (a ÷2 + a ÷ 2 ) = (a ÷ 3 + a ÷ 3 + a ÷ 3 ) =  a(a ÷a) etc..(one of the  easiest loop for unlimited number of equations or formulas through iteration)
  6. xy  = (xy ÷ 2 + xy ÷ 2) =  (xy ÷ 3 + xy ÷ 3 + xy ÷ 3 ) = a(xy ÷a) = v = (v ÷3 + v ÷ 3 + v ÷ 3) = (v÷ 4 + v ÷ 4 + v ÷ 4 + v ÷ 4) =  a(xy ÷a) etc..etc…
  7. zy  = (zy ÷ 2 + zy ÷ 2) =  (zy ÷ 3 + zy ÷ 3 + zy ÷ 3 ) = a(zy ÷a) etc..
  8. x^2 = y^2 = z^2 = v^2 = (x^2 ÷ 2 + x^2 ÷ 2) =  (y^2 ÷ 3 + z^2 ÷ 3 + v^2 ÷ 3 ) = a(x^2 ÷a) = a(y^2 ÷a) = a(z^2 ÷a) = a(v^2 ÷a) etc..(where x = y = z = v)
  9. xy^2  = (xy^2 ÷ 2 + xy^2 ÷ 2 ) =  (xy^2 ÷ 3 + xy^2 ÷ 3 + xy^2 ÷ 3 ) = (x ÷ 2 +  x ÷ 2)*y^2 = a(xy^2 ÷a) etc..
  10. zy^2  = (zy^2 ÷ 2 + zy^2 ÷ 2 ) =  (zy^2 ÷ 3 + zy^2 ÷ 3 + zy^2 ÷ 3 ) = a (z÷a) * a(y^2 ÷a) = a(zy^2 ÷ a ) etc.
  11. zv^2  = (zv^2 ÷ 2 + zv^2 ÷ 2 ) =  (zv^2 ÷ 3 + zv^2 ÷ 3 + zv^2 ÷ 3 ) = a (z÷a) * (v^2 ÷ 2 + v^2 ÷ 2) = a(zv^2 ÷ a ) etc.
  12. y^n =  (y^n ÷ 2 + y^n ÷ 2 ) =  (y^n ÷ 3 + y^n ÷ 3 + y^n ÷ 3 ) = a  = a(y^n ÷ a ) etc.
  13. (v(y^n))^2 =  ( (v(y^n))^2 ÷ 2 +  (v(y^n))^2 ÷ 2 ) = ( (v(y^n))^2 ÷ 3 +  (v(y^n))^2 ÷ 3 + (v(y^n))^2 ÷ 3 ) = a( (v(y^n))^2 ÷ a ) etc..
**
  1. x^n ÷ x^ny^n ÷ x^n = z^n ÷ x^ny^n ÷ z^n etc..
  2. x^n ÷ z^ny^n ÷ x^n = z^n ÷ z^ny^n ÷ z^n etc..
  3. x^n ÷ x^ny^n ÷ x^n ÷ x^ny^n = z^n ÷ x^ny^n ÷ z^n ÷ x^ny^n etc..
  4. x^n ÷ z^ny^n ÷ x^n ÷  z^ny^n = z^n ÷ z^ny^n ÷ z^n ÷ z^ny^n etc.

  1. x^n ÷ z^nv^n ÷ x^n = z^n ÷ z^nv^n ÷ z^n etc..
  2. x^n ÷ (z^nv^n)^n ÷ x^n = z^n ÷ (z^nv^n)^n ÷ z^n etc..
  3. x^n ÷ z^nv^n ÷ x^n ÷ z^nv^n = z^n ÷ z^nv^n ÷ z^n ÷ z^nv^n etc..
  4. x^n ÷ (z^nv^n)^n÷ x^n ÷  (z^nv^n)^n = z^n ÷ (z^nv^n)^n ÷ z^n ÷ (z^nv^n)^n etc.

  1. x^n ÷ z^n÷ x^n = z^n ÷ z^n÷ z^n = y^n ÷ z^n÷ y^n etc..
  2. x^n ÷ x^n  ÷ x^n = z^n ÷ x^n ÷ z^n = y^n ÷ x^n÷ y^n etc..
  3. y^n ÷ y^n÷ y^n = z^n ÷ y^n÷ z^n = x^n ÷ y^n÷ x^n etc..
  4. x^n ÷ z^n ÷ x^n ÷ z^n = z^n ÷ z^n ÷ z^n ÷z^n =  y^n ÷ z^n ÷ y^n ÷z^n netc..
  5. x^n ÷ x^n ÷ x^n ÷ x^n = z^n ÷ x^n ÷ z^n ÷ x^n = y^n ÷ x^n ÷ y^n ÷x^n etc.
  6. y^n ÷ y^n ÷ y^n ÷ y^n = z^n ÷ y^n ÷ z^n ÷ y^n = x^n ÷ y^n ÷ x^n ÷y^n etc..
**
  1. x ÷ xy^n ÷ x = z ÷ xy^n ÷ z etc..
  2. x÷ zy^n ÷ x= z^n ÷ zy^n ÷ z^n etc..
  3. x ÷ xy^n ÷ x ÷ xy^n = z ÷ xy^n ÷ z ÷ xy^n etc..
  4. x ÷ zy^n ÷ x ÷  zy^n = z ÷ zy^n ÷ z ÷ zy^n etc.



19) Conversation and Inverse of y  using Constant 1 where x and y # 0:
a) y = 1÷y÷(1÷y)÷(1÷y) = 1÷y÷1÷(1÷y)÷(1÷y) =  etc...
b) y = x÷y÷x÷(1÷y)÷(1÷y)  = x÷xy * (1÷y)^2 = x÷y÷x÷y÷(1÷y)÷(1÷y) ÷(1÷y)= x÷xy^2* (1÷y)^3 = etc..

Virtually there is no limit in numbers of  constant equality equations and values that can be formed, however above can be considered as a standard set that can be used in combination based on value equality. The selection of combination  depends on requirement for specific applications or use. Trigonometry functions, Quadratic, Symmetry, Calculus or any other formulas or equations from any subject or combination will fit well within the above constant equality  equations and models.

Following is the sample calculation  e = mc^2 and e(quantum) = hf

If m = c^2 ,  h = f and # = not equal

e = c^4 # h^2
  e = c^4 *( h^2÷h^2)  # h^2 * (c^4 ÷ c^4)
e =  c^8 *( h^2)  # h^4* (c^4 )


1)  e =  c^8 *( h^2) ÷ ( h^4* (c^4 ) * c^8 *( h^2))  = h^4* (c^4 )÷ (h^4* (c^4 ) * h^4* (c^4 ))
e = c^8 * h^2 ÷ ( h^6* c^12) =  h^4* c^4 ÷ (h^8* c^8 )


You can have many more constant Equality Equations for the above sample calculation of e as per the requirement of applications bridging into total equality.

Observation from the sample calculation is that Constant wave height and fixed wavelength with constant pattern and vibration on fixed velocity may transmit energy from a point to another point without support of any wires and with support of a channel to other dimensions even.

For more samples check the following link:

http://constant9.blogspot.in/2018/03/quantum-meet-relativity-equations.html


History of the equation:

http://constant9.blogspot.in/2016/08/moving-into-any-direction-and-reaching.html



Graph of constant equality equations:



If you want to find constant equality equation for any specific formula and it's observation, you can contact me. Remember knowledge is free but not time.


Sunday, March 4, 2018

Quantum Meet Relativity Equations : ((8πGn÷C^4)Tuv)^2*HW ÷ (HW^2((8πGn÷C^4)Tuv) * ((8πGn÷C^4)Tuv)^2)*HW = HW^2*((8πGn÷C^4)Tuv) ÷ (HW^2*((8πGn÷C^4)Tuv))^2


In the following mathematical  model and equations quantum meet relativity and vice versa.  

Equation : ((8πGn÷C^4)Tuv)^2*HW ÷ (HW^2((8πGn÷C^4)Tuv) * ((8πGn÷C^4)Tuv)^2)*HW = HW^2*((8πGn÷C^4)Tuv) ÷ (HW^2*((8πGn÷C^4)Tuv))^2

General Relativity :

(8πGn÷C^4)Tuv

Quantum  General Time dependent:  HW

(((8πGn÷C^4)Tuv)*HW) ÷ HW # ((HW*(8πGn÷C^4)Tuv)) ÷ (8πGn÷C^4)Tuv

((8πGn÷C^4)Tuv)^2*HW # HW^2*((8πGn÷C^4)Tuv)

(# means not equal)

1) ((8πGn÷C^4)Tuv)^2*HW ÷ (HW^2((8πGn÷C^4)Tuv) * ((8πGn÷C^4)Tuv)^2)*HW = HW^2*((8πGn÷C^4)Tuv) ÷ (HW^2*((8πGn÷C^4)Tuv))^2

2) HW^2((8πGn÷C^4)Tuv))÷ (HW^2((8πGn÷C^4)Tuv) * ((8πGn÷C^4)Tuv)^2)  = ((8πGn÷C^4)Tuv)^2)*HW ÷ ((8πGn÷C^4)Tuv)^2)*HW)^2

3) ) ((8πGn÷C^4)Tuv)^2*HW ÷ (HW^2((8πGn÷C^4)Tuv)^2 * ((8πGn÷C^4)Tuv)^2)*HW = HW^2*((8πGn÷C^4)Tuv) ÷ (HW^2*((8πGn÷C^4)Tuv))^3

4) HW^2((8πGn÷C^4)Tuv))÷ (HW^2((8πGn÷C^4)Tuv) * ((8πGn÷C^4)Tuv)^2)^2  = ((8πGn÷C^4)Tuv)^2)*HW ÷ ((8πGn÷C^4)Tuv)^2)*HW)^3

from the above equations quantum and relativity meet even in other dimensions. There no way to say that they are against each other except the observational difference.

In simpe sense, the graph of the above equations are as follows :

  1. x ÷ xy
  2. x ÷ x^2
  3. y ÷ x^2y
  4. y ÷ y^3

This model will match any equations to itself or with any other equations without any prejudice observation and will return a constant value, if the equation(s) is rearranged.

Sunday, February 25, 2018

Zero Gravity and Anti gravity Space Adjustment r = ((m1*m2+m1*m2)÷2F )

Zero Gravity  and Anti gravity Space Adjustment where g=r in
f = g(m1*m2)/r^2
= r((m1*m2)÷2)+r((m1*m2)÷2)/r^2
=(( m1*m2)÷2r)+((m1*m2)÷2r)

= (m1*m2+m1*m2)÷2r or 2g
= (m1*m2+m1*m2)÷ 1.3348E−10


Gravity do really exist based on above observation ?
What happening is space adjustment in internal structure of an object with a mass and r = ((m1*m2+m1*m2)÷2F )
may be the required space adjustment in vector field within each object in its nucleus proportionately to change the gravitational constant itself.
if we consider m1 and m2 = G then the mathematical possibility shows G^2+G^2 ÷2F to be Zero gravity and larger than this value may be anti-gravitational.

If your mind is not clear on the logic behind the mathematical possibility, just graph the equations in a 3D Grapher as follows :
x = sine(x)
x 1= cos(x)
x2 (x,z)=( G^2 + G^2)÷2r
y (x)=  (G^2 + G^2)÷2x2
z (x,y)=   (G^2 + G^2)÷2x2


Science Fiction and Fact thoughts on Constant Motion : If a zero gravity object or anti - gravity or negative gravity object in circular motion and exposed to gravity such object will have a curved motion <= 180° or <= π radian ( eg: gravity exposed at sine(45°) may give a value >  sine(45°) and <=sine (225°) , the minimum value  will always be more than sine(135°). It may be similar to the graph function f(x)=sine(x) or cos(x).

And if gravity exposed Sine(0° to 50°) give a curved motion <=180° then Gravity exposed Sine (310° to 360°) must also give an exactly opposite curved motion, both these motion will have a displacement of the object in a point in straight line and such displacement can varying based on force and velocity. The curved motion itself can be changed to spiral or helical motion based on the force applied on the varying radius, force,  angle or velocity.

If an object named A contain two parts and one part(Object1) subject to Zero gravity or Anti-gravity or Negative gravity  as Static Object1 and Another in part (Object2) is also same type of Anti-gravity or Zero Gravity or Negative Gravity or Gravitational in Circular Motion  and these two objects are exposed to same gravity or varying gravity to each other these may produce their  own gravitational fields and Object A (containing Object1 and Object2) will move in the field of higher Gravity Object and the length of curved motion will vary based on the radian of the gravity exposed to each other. If gravity is applied on varying 'radius’, and angles ,the object may have helical motion or spiral motion in varying radius and these object will be always have variable speed and not limited by any constant including speed of light.

Real world fantasy observation :  if moon as sphere had a only a radian part on its sphere, the moon will not be in complete circular motion and may start moving away from earth and solar system , still it find a gravitational equality. Which means partly gravitational or anti-gravitational is already capable of self motion in the field of an object of higher Gravitational Object , once the object set to unrest by a Force. However the motion will not be same in momentum or velocity for moon, it can some time curved, helical, spiral in various radius because when it enter and changed into the gravitational field of Sun or another plan or Star. As long as there is another gravitational field moon will be in constant motion. This journey of moon may start to reverse to a reverse velocity (back to point of origin) when moon will encounter a gravitational opposite having exactly opposite or more than the Gravitational force of moon moving same like moon and moon enter in that gravitational field. If moon never find such a filed, moon will be in constant motion and will collide ,if and only if it ever find encounter into a gravitational opposite or gravity neutral field. This may be the reason that some planets and stars are always on constant motion.If a sphere has a partial Anti-gravity on any of it's pole or core and if the core produce magnetic waves such magnetic wave will be move in one direction.

Sunday, February 4, 2018

1^n = ( (a( 4 ÷ π))* (b( 4 ÷ π) )÷ ab)


1^n = ( (a( 4 ÷ π))* (b( 4 ÷ π) )÷ ab)

1 ^3 = 1.2732395447351

Dimensional convertibility. This observation is basically for splitting a cubes or squares calculating the average value. As you can split a cube  into two equal pieces, one of its side will be greater than the other two side of the same face. Similar observation can be seen in a square too.

The formula is as follows :

1^3 = ((( 4 ÷ (2π ))^2)π)
      
     = 1.2732395447351…..
the shortcut is :

1^3 = 4 ÷ π
      = 1.2732395447351

Logic and explanation behind formula:
  1. Perimeter of one face of cube or square = 4
  2. Find the radius by dividing it with 2π
  3. Apply the volume formula of cylinder is πr^2h
  4. h = 1.
  5. 1 is undefined base dimensions and can be defined to any types of unit of measurements like ara, volume, energy etc..

Hence 1^3 ÷ 2 or 1 ^ 2 ÷ 2 =  0.6366197723675…..
1^3÷1^2 = 1.5*(4÷π)÷(4÷π)=1.5 (is the minimum value)


If you are curious to know 1^n in the model of above observation for eg: a) 1^7 = ? or  b) 1^ 8 etc..

Considering a possibility of 2 squares and 1 cube ie. 1^2*1^2*1^3   or 2 cubes and an undefined 1 ie. 2(1^3 )*1^1 or 3 squares and an undefined 1 ie.3(1^2)*1^1 one could define a a average possible value for  total numbers of complete squares alone as 3 and total number of complete cubes as 2  ie. 3(1^2)*2(1^3)and also the same value reflect for 1^n and the calculation is :

=3(1.2732395447351)*2(1.2732395447351)

= 9.7268336296644 ÷ 6

= 1.6211389382774

! ( 6 = 3*2 is the products of total numbers of complete squares and cubes )

So the possible average value of

1^n = ( (a( 4 ÷ π))* (b( 4 ÷ π) )÷ ab)
      

where n  is considered here a positive integer > 3
n can be a combination of square(s)  and cube(s) or square(s) alone or cube(s) alone.

a = total number of complete square alone.

b = total number of complete cubes alone.

Square and Cube are dimensions. In real world you can observe it as the shadow of a 3D object in various brightness of a same color of light in the same angle.

In real world example 3 blue lights  of different brightness in same angle. The first light source produce a 2D (square) shadow and the 2 and 3 light sources  also produce shadow for each but these light sources also cause  some part of shadow to fade from 3 of the  light sources. If one calculated the area of first shadow and wanted to know the average value of shadows with respect to 3 light sources and to compare with the value of first shadow is 1^3 is the value.

The above formula overcome the  limitation of placing many light sources in same angle in same location point focusing the same 3D object.
Some weird thought on usage eg: e=mc^2 , e÷ mc^2 or mc^2÷e = 1, 1= 1÷(4÷π) = 1÷(1*1*1 or 1^2) cube or square dimensional value of energy.
When m=c^2, 1 = c^4÷c^4 =  , 1 = (1÷(( e÷ c^4)*2(4÷π)) = 3.18086256175*10^21


!! Any object that with a constant slow  speed(vibration) per second of :  1÷(2*(4√3.18086256175E21) )
seems to have the quantum value of energy and may be capable of inter dimensional conversation or pass through another object or may allow another object to pass through. The best assumption for an experiment in vacuum. It may also possible to try with value as m = c and c^3 instead of c^4. However in dimensional conversation c^3 don't seem to be adequate.


In preview of above there are some raw thoughts regarding negative time or past time and future time as concepts.


Negative time is past time frame and positive time is future time frame.

Some science fiction thought are there, if an object of 1 meter radius rotate at 232457 rotation per second, positioned at an angle 48.83° left and above to the sun set angle(farthest angle from west in the previous year) , it's shadow likely to disappear. And 2 * 232457 rps  (anti clock wise) will likely to take the object in the negative time or past appearance of the object, if the shadow of the object appear in front of the object. And clockwise rotation likely to take positive time or future appearance of the object.!!